Pengaruh Metode Tasmi’ Terhadap Kualitas Hafalan Al-Qur’an Siswa Di MTsN 4 Madina - Rizka Rahmadani (-, 2023)
This study aims to determine the results of the quality of students' Al-Quran memorization and the effect of the Tasmi' method on the quality of memorization.  The method used in this research is quasi-experimental with a sample of 30 students.  As for the data measuring devices used are observation sheets, questionnaires and documentation.  The results of this study were analyzed using the SPSS version 25 application. The results showed that the average score in the experimental class was that the class using the Tasmi' method was higher than the average value in the control class.  both in terms of fluency of memorization, fluency of letters, signs of waqaf, tajwid and memorization of rote readings.  so that it can be concluded that there is a difference between users of the Tasmi' method and classes that do not use the Tasmi' method on the results of the quality of students' memorization of the Qur'an in Al-Quran subjects at MTsN 4 Madina, Siabu district.